Mapping Karakter dalam Meningkatkan Kesesuaian Individu dan Struktur Peran di Lingkungan Organisasi Pesantren - Mitsalul Hafidz; M. Ali Fani (CV. Laskar Karya, 2025)
The mismatch between individual character and structural roles in pesantren organizations often leads to decreased work effectiveness, unequal task distribution, and relational conflicts among administrators. This study aims to examine character mapping strategies as an adaptive approach to enhance the alignment between individuals and structural roles. A descriptive qualitative method was employed, involving leaders and active administrators in the Jalaluddin Ar-Rumi Division of Pondok Pesantren Nurul Jadid. Data collection techniques included in-depth interviews, non-participatory observation, and documentation, analyzed using Miles & Huberman’s interactive model. The findings reveal that the absence of a character mapping system results in improper role placement, low motivation, and symbolic performance dominance. The proposed character mapping strategy comprising initial identification, self-assessment, deliberation forums, adaptation period, and light monitoring proves effective in improving role-person fit and increasing organizational engagement. The novelty of this study lies in the development of a character mapping model contextualized to pesantren culture and integrating psychological approaches in organizational management. It recommends reformulating pesantren HR systems based on individual potential to enhance organizational efficiency and sustainability.